Molten Carbonate Fuel Cells for 90% Post Combustion CO2 Capture From a New Build CCGT - Ferguson, Suzanne; Tarrant, Anthony (Frontiers in Energy Research, 2021)
This paper presents the findings of the techno-economic assessment undertaken by Wood for the UK Government Department for Business, Energy and Industrial Strategy on the large-scale deployment of Molten Carbonate Fuel Cells (MCFCs) for post-combustion CO2 capture integrated with a new build combined cycle gas turbine power plant for the generation of low carbon electricity. Based on a new build power plant to be installed in the North East of England, with a power train comprising two trains of H-class gas turbines each with a dedicated steam turbine, the configuration presented utilises MCFCs between the gas turbine exhausts and their heat recovery steam generators and cryogenic separation for unconverted fuel recycle and CO2 purification. It was found that the proposed configuration could achieve 92% CO2 capture from the overall power plant with MCFCs while achieving 42% of additional new power production with only 2.6 %-points of thermal efficiency penalty compared to a conventional proprietary amine benchmark. While the total project capital cost increased by 65%, the high overall thermal efficiency and additional power generated resulted in a Levelised Cost of Electricity almost identical to the benchmark at £70/MWh (US97/MWh). A number of areas are identified for potential further improvement in this scheme. It is concluded that use of MCFC technology, which also has the capability to be tailored for hydrogen production and combined heat and power services, shows significant potential to be competitive with, or exceed, the performance of current state of the art technologies for post-combustion CO2 capture.